Effect of Hall Current on MHD Non-Newtonian Unsteady Casson Fluid Porous Rotating Disk Flow with a Uniform Electric Field - Maleque, Kh. Abdul (AIUB Journal of Science and Engineering (AJSE), 2017)
The effects of Hall current and a uniform electric field on non-Newtanian casson fluid porous rotating disk flow are examined. A uniform angular velocity, an axial uniform magnetic field and the Hall current are taken into considered. Examples of Casson fluid include jelly, tomato sauce , honey , soup and concentrated fruit juices, ect. Human blood can also be treated as Casson fluid. Considering the suitable similarity parameters the governing equations of the problem are then transformed into the non-linear ordinary differential equations. The ordinary similarity differential equations are then solved numerically by six order Runge-Kutta method and shooting method using the Nachtsheim- Swigert iteration technique.